Association between Lifestyle Factors and Preterm Delivery: A cross-sectional observational study in Mosul City (Eurasian Medical Research Periodical, 2023)
Preterm birth (PTB) is a major public health concern that affects millions of newborns and their families each year. It is defined as the birth of a baby prior to 37 weeks of gestation. This study aimed to find the association between Maternal Lifestyle with preterm delivery in Mosul city